The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/483282
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic Characterization, and Biological Evaluation Studies of 5-Bromo-3-(((hydroxy-2-methylquinolin-7-yl)methylene)hydrazono)indolin-2-one and Its Metal (II) Complexes

Abstract: The Schiff base ligand 5-bromo-3-(((8-hydroxy-2-methylquinolin-7-yl)methylene)hydrazono)indolin-2-one (BHMQMHI) was prepared via condensation of 5-bromo-3-hydrazonoindolin-2-one and 7-formyl-8-hydroxy-2-methylquinoline and its Co(II), Ni(II), Cu(II), Zn(II), Cd(II), and Hg(II) complexes have been synthesized and characterized by elemental analysis, conductance data, magnetic susceptibility measurements, IR, UV-Vis, mass spectrometry, 1H NMR, ESR, XRD, and thermal studies. By these spectral studies it is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…This was further supported by the downward shift in the phenolic ν(C−O) group observed at 1266 cm −1 in the free ligand to the region 1237–1246 cm −1 [ 22 ] upon complexation. This shift confirms the coordination of the phenolate oxygen to the metal ion [ 14 , 20 ].…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…This was further supported by the downward shift in the phenolic ν(C−O) group observed at 1266 cm −1 in the free ligand to the region 1237–1246 cm −1 [ 22 ] upon complexation. This shift confirms the coordination of the phenolate oxygen to the metal ion [ 14 , 20 ].…”
Section: Resultssupporting
confidence: 64%
“…The infrared of BEB displayed characteristic bands at 3404 cm −1 that could be attributed to the ν(O‒H) stretching vibrations in the free Schiff ligand [ 10 , 16 ]. The absence of this band in the spectra of the complexes is an indication of deprotonation and involvement of the phenolic hydroxyl group of the ligand during bond formation with the copper ions [ 19 , 20 ]. The medium and broadband at 3378–3396 cm −1 in the spectra of the Schiff base-Cu(II) complexes are assigned to the ν(OH) frequency of the water molecules in the complexes [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicated the involvement of N-atom of the azomethine (-HC=N) group and carbonyl oxygen in complex formation 10,11 and the band at 3207, 1606 cm -1 in the spectra of all the complexes were assigned to ν(N-H) and ν(C=N) of the ketimine moiety remain almost unaffected, indicating the non participation of these groups in coordination. 12 Therefore, the IR spectral data indicated that the coordination of hydrazone Schiff base to metal ion occurred through the N-atom of the azomethine (-C=N) group and the O-atom of carbonyl (C=O) group. Assignment of the proposed coordination sites was further supported by the appearance of medium bands at 453-499 cm -1 and 351-379 cm -1 due to M-N and M-Cl stretching frequencies, respectively.…”
Section: Ir Spectral Studiesmentioning
confidence: 96%
“…Constructed on the ''MEP'' , one can mostly order the electron-rich area with has red color of a map which prefer site for electrophilic attack. However, the electron-poor region has blue color favors site for nucleophilic attack [30]. Nevertheless, the green region point to neutral electrostatic potential region.…”
Section: Page 5 Of 10mentioning
confidence: 99%